Las asociaciones de banco de tiempo: entre la reciprocidad y el mercado - Sanz Casas, Gonzalo (ENDOXA, 2002)
The author argues that reciprocity has to be refined if we want to use it as a valid tool of analysis for the interpretations of relationships not mediated by the market or by the Welfare State.